SPEAKING ACTIVITIES APPLIED BY THE TEACHER IN TEACHING SPEAKING OF THE ELEVENTH GRADE SMA N 2 BANGKINANG - Vitri Angraini Hardi (Universitas Pahlawan Tuanku Tambusai, 2019)
Speaking is one of the skills which are taught in English. It is intended to express our ideas or our thought. In teaching and learning activities, teaching speaking is possible to do by applying some speaking activities such as interview, discussion, role play, etc. The speaking activities are used based on the purpose of the learning outcome. The teacher have to be able to decide the appropriate speaking activities used in teaching speaking. However, some teachers are not accustomed with the variation of speaking activities. The tendency of using the discussion activity is still in use by the teacher. In this research the researcher found some speaking activities which were applied by the second year students at SMA N 2 Bangkinang namely interview, discussion, dialogue, question answer, and reporting. This research is descriptive research. There are three instruments used in this research, observation sheet, interview, and documentation. Technique used in analyze the data is based on three indicators of speaking activities. They are type of activity, organizational form, and instruction. The Findings found that from five kinds of speaking activities four of them were classified as communicative activities and the rest were classified as quasi pre communicative. Based on the organizational form, it was classified as group work, pair work, and whole class teaching. Meanwhile, based on the instruction given, mostly the teacher used target language (English), but at the second meeting is mostly used combination (mother tongue and target language). Furthermore, based on the length of instruction, mostly the teacher used Long instruction. And the last one, based on support for instruction at the first meeting, the teacher used paralinguistic, written clues, and restatement. Meanwhile at the second meeting, the teacher used paralinguistic, visual, written clues, and restatement.